Review on efficient protocol for tissue culture of rice, (Oryza sativa L.) / Mohamad Aszrul Amiezan Abdullah - Abdullah, Mohamad Aszrul Amiezan (Faculty of Plantation and Agrotechnology, 2018)
Rice or its scientific name, Oryza sativa L. is a main basic food. Rice became the most important crop in the global as most people in the world consume rice as their major daily consumption for their protein and energy source. Growth of paddy declined due to biotic and abiotic stress. Thus plant tissue culture technology is one of biotechnology approaches that used to propagate the plant. Research studies by previous researchers is to find the proximate tissue culture techniques or approaches for rice tissue culture. Some other factors such as tissue culture medium, plant growth regulators, carbon sources, gelling agents and photoperiod need to be considered in order to achieve successful tissue culture. From the review paper, the most common medium used in micropropagation is MS medium (Murashige and Skoog, 1962) with the supplementation of various plant hormones and other supplements. The right amount of plant hormones are essential to ensure better callus induction and plantlet regeneration. Auxin and cytokinins are the kind of plant hormones that commonly used in plant micropropagation. The optimum treatment type for inducing callus for almost rice genotypes is MS media containing 2 mgl-1 2, 4-D. The optimum plant hormones combination for regeneration is the mixing of 2 mgl-1 BAP, 0.5 mgl-1 NAA and 0.5mgl-1 Kin.